Pot zakonodajnega akta z vidika predsedstva Sveta Evropske unije - Pate, Janez (Javna uprava, 2021)
The author presents the path of the legislative act, in this case the proposal of a Regulation on European data governance, from the perspective of the Presidency of the Council of the European Union. He describes his experience while performing the duties of an attaché at the Permanent Representation of the Republic of Slovenia in Brussels during the Slovenian Presidency of the Council of the EU in 2021. The author defines concepts such as: what the Presidency of the EU Council means, what tasks the eighteen- and six-month Presidency programme includes, presents the work of the Permanent Representation of Slovenia to the EU and explains what Coreper and working parties are. Simultaneously, he describes the work of his team that is covering the area of digital files within the working party on telecommunications and information society. The author continues by describing the ordinary legislative procedure on the proposal of the Regulation at all phases, which was successfully concluded with an agreement with the European Parliament on the final content of the act, which is crucial for the development of the European data economy. Finally, the author explains how the current situation of the Covid-19 pandemic affected the performance of their work during the Presidency and concludes by emphasising the importance of digital tools, services, and everything related to the use of information and communication technologies.
Keywords: Council of the European Union; digitalisation; digitalizacija; European Parliament; Evropski parlament; legislation; predsedovanje; presidency; Svet Evropske unije; zakonodaja